Pengaruh Profesionalisme Guru dan Budaya Sekolah Terhadap Kemampuan Literasi Dasar Siswa Madrasah Ibtidaiyah - Lalu, Awaludin Akbar; Muslihan; Husnawati (LPPM Press, 2024)
This study aims to determine the magnitude of the influence of several variables of teacher professionalism and school culture together on students' basic literacy abilities at Madrasah Ibtidaiyah (MI) in Suralaga District using 28 teachers and 560 students as respondents. This study uses an ex-post facto approach. Data were collected using a school culture teacher professionalism questionnaire, and tests of students' basic literacy skills. Data analysis using simple correlation, simple regression, and multiple regression. The results showed that there was a significant influence: (1) teacher professionalism on students' basic literacy skills with a determination of 22.4% and an effective contribution of 20.9%, (2) school culture on students' basic literacy skills with a determination of 22, 8% and an effective contribution of 21.3%, (3) together the professionalism of teachers and school culture on the basic literacy abilities of students at MI in Suralaga District with a determination of 42.2%. Teacher professionalism and school culture can be used as predictors of students' basic literacy abilities